Comparison of matrix converter and common converter for induction motor application using MATLAB - Nor Afidatul Asni Semsudin, Semsudin (2010)
Among the most desirable features in power frequency changers are simple and compact power circuit, generation of load voltage with arbitrary amplitude frequency, regeneration capability, and operation with unity power factor for any load. These ideal characteristics can be fulfilled by matrix converter (MC) which is become increasingly attractive for the AC drive applications. It has the potential to replace the conventionally converter. Matrix converter is a new type of direct AC to AC converter which converts input line voltage into variable voltage with unrestricted frequency without using an intermediate DC link circuit. MC uses the space vector modulation technique to control the input power factor which is the simpler method than the other control modulation. The objectives of the project are to implement the MC to control speed and torque of induction motor by using MATLAB Simulink and to design the common converter for induction motor application besides to compare the performance of the induction motor by using matrix converter and common converter. The simulation results of voltage and current waveform will be achieved if the project is implemented successfully